The Role of Special Assistant Teachers on Speech Delay Students' Social Interaction in Elementary Schools: Peran Guru Pendamping Khusus Terhadap Interaksi Sosial Siswa Speech Delay di Sekolah Dasar - Rahmawati, Anisa Ramadhani; Wachidah, Kemil (Indonesian Journal of Education Methods Development, 2022)
This research is motivated by the importance of social interaction that starts early. So that special assistant teachers play a role in improving the social interaction skills of speech delay students. The purpose of this study was to determine the application of the role of the special assistant teacher to the social interaction of speech delay students and the obstacles of the special assistant teacher (GPK) in implementing their duties on the social interaction of speech delay students. The researcher uses a case study qualitative research method. Data collection techniques used are non-participant observation, structured interviews, and documentation. The research subjects are special accompanying teachers and their accompanying speech delay students. The result of the research is that special assistant teachers play a role in social interaction by accompanying students, ensuring student activity and guiding students to be able to socialize by slowly eliminating their egocentric nature. The obstacle for GPK in implementing its duties is that when the ATF is critical, it is difficult to accept suggestions from others. So that it can be said that social interactions arise due to imitation factors and suggestions given by GPK.